Effect of heat treatment on the properties of solution annealed and hot rolled Incoloy 20. (2021) - Natesh, M.; Venkata Sumanth, Bandi; Kumar Reddy, Kasu Vinay; Nadeem, S.K.; Sathishkumar, M.; Manikandan, M.; Arivazhagan, N.
Abstract: Microstructural and mechanical properties of Incoloy 20 were investigated in the as-received (hot rolled and solution annealed) and various heat-treated conditions. Particular interest has been shown to identify the characterization of primary and secondary precipitates at elevated temperatures. As-received Incoloy 20 microstructures revealed fine and twin-annealed grain structures. Incoloy 20 is heat-treated with three different temperatures (700°, 900°, and 1100 °C) at duration of 5 and 10 h. Reduction of segregation and coarsened grain structures is noticed while increasing the homogenization temperature. However, the grain structure remained same with diminution of strength and increased ductility. After the heat treatment, the tensile strength reduced gradually while increasing the temperature for Incoloy 20. The microstructures of the heat-treated specimens revealed the porous structure at grain boundary regions majorly at 900 °C with both durations. In this study, optimal operating temperature for Incoloy 20 is 700 °C where strength remain similar to base metal and also similar microstructure noticed.